2013
DOI: 10.1371/journal.pone.0074517
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Tuberculosis: Mycobacterium tuberculosis Strains and Host Risk Factors in a Large Urban Setting in Brazil

Abstract: BackgroundFactors related to the development of extrapulmonary forms of tuberculosis (EPTB) are still poorly understood, particularly in high-endemic countries like Brazil. The objective of the paper is to determine host and Mycobacterium tuberculosis (MTB) strain-related factors associated with the development of EPTB in Espírito Santo state, Brazil.Methods and FindingsWe conducted a retrospective laboratory-based surveillance study of new tuberculosis (TB) cases diagnosed in Espírito Santo state, Brazil betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
1
24
1
2
Order By: Relevance
“…Using the modified Newcastle-Ottawa criteria ( Appendix Table 1 ), four of the studies [17, 20, 25, 29] had a low risk of bias, ten [18, 19, 21, 22, 24, 26-28, 30, 31] had a medium risk of bias and two [23, 11] had a high risk of bias. Despite the cross-sectional design, studies by Wilkinson and Moore; Gonzalez et al; Fiske et al; and Sama et.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the modified Newcastle-Ottawa criteria ( Appendix Table 1 ), four of the studies [17, 20, 25, 29] had a low risk of bias, ten [18, 19, 21, 22, 24, 26-28, 30, 31] had a medium risk of bias and two [23, 11] had a high risk of bias. Despite the cross-sectional design, studies by Wilkinson and Moore; Gonzalez et al; Fiske et al; and Sama et.…”
Section: Resultsmentioning
confidence: 99%
“…High heterogeneity remained in another sensitivity analysis where EPTB was defined as “EPTB only” (“EPTB+ PTB” cases were excluded from the analysis). When the Gomes paper [19] was excluded in another sensitivity analysis because it had much higher estimates of the odds ratio compared to other studies, high heterogeneity persisted (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…1 It is widely reported that EPTB occurs more frequently in immunocompromised patients. 8,15,16 EPTB accounts for more than 50% of tuberculosis cases in HIV/AIDS patients as compared to 15-20% of TB cases in immunocompetent patients. 10,17 In fact, EPTB is considered an AIDS defining disease.…”
Section: Introductionmentioning
confidence: 99%
“…Factors most frequently found are: poverty, malnutrition, overcrowding, lack of ventilation and lighting in homes, alcohol, smoking and other drugs, pregnancy, corticosteroids use, lack of access to merg services and presence of other associated conditions such as diabetes (Gomes et al, 2013). Household contacts with TB infected merg also a known and risk factor for development tuberculosis, especially in endemic areas (Fox et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Household contacts with TB infected merg also a known and risk factor for development tuberculosis, especially in endemic areas (Fox et al, 2013). HIV infection has joined the long list of risk factors and confers increased risk for active Tb (Gomes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%